Indonesia in transition. Rethinking 'Civil Society', 'Region', and 'Crisis' - [Tidak Terdaftar] (Pustaka Pelajar, 2004)
This book is the result of a workshop held at the campus of Universitas Indonesia from 24-27 August 2003. The Meeting was hosted bu LabSosio, the research centre of the Department of Sociology of the UI. The meeting was organized in cooperation with the Royal Netherlands Academy of Sciences (KNAW) and generously co-sponsored by the Rector and the Faculty of Social Sciences of the Universitas Indonesia, the International Institute of Asian Studies (IIAS) , and the IndoverBank.